Peran Patroli Dialogis Satuan Sabhara Polres Ciamis Dalam mengurangi Pencurian Kendaraan Bermotor Melalui Metode Community Policing di Wilayah Ciamis - Arthur Siagian (Advances in Police Science Research Journal, 2020)
Vehicle theft is one type of crime that still happen in Indonesia. Vehicle Theft become one amongst four crimes that get the attention in the ranks of all Indonesian Police across the country. But in reality, it is the duty of dialogic patrol’s role from Sabhara unit to prevent vehicle theft from happening. Research method used in this research is qualitative method. On the other hand, Data that will be analyzed in this research is interview data that has been done to people in the society, the offender, police in Polres Ciamis, studying documents, and observation to the performance of dialogic patroll. Result of the research is that the performance of Community Policing patrol by Polres Ciamis Sabhara Unit still have many problem. One of those problem is the mindset of police patrol personnel that still think that vehicle theft is not a significant problem. Not only that, Lack of personnel, facilities, supportive equipment, and most of all is that many principal of Community Policing has not efficiently being implemented in the society and the police personell. The problem and lackness that happen inside the dialogic patrol makes the offender do their crime according to the theory analysis of Routine Activity and Rational Choice. The conclusion is that the factor that slows down the dialogic patrol is divided by two which is internal factor and external factor. Police has not yet reach all parts and layers of society, especially police personel that directly do the patrol duty. Police must reach and interact with all parts and layers of the society. Good emotional relation between the police and the society is very eseential to create a Community Policing environment. Based on the explanation above the writer deliver a few recommendation. The recommendation to solve personell problem is to requisition extra personell from the higher authority. Another recommendation that writer delivered is patrol unit card program that could be socialized so the Community Policing culture could be created in the society.